Engineering Application of Nanomaterial and Ferroelectric Domain Polarization to the Dynamic Structure of the Surrounding Rock of Heavy-Duty Railway with Small Clear Intersection Tunnel - Xiaotian Hao; Hailong Wang (Advances in Materials Science and Engineering)
With the development of national railways and railways as one of the important channels for heavy-haul transportation, the construction of heavy-haul railways must be a rapid development, which makes it inevitable that the heavy-duty situation of small-distance interchange tunnels will appear. Nanomaterials refer to materials that have at least one dimension in the three-dimensional space in the nanoscale range (1 nm∼100 nm) or are composed of them as basic units. Ferroelectric domain polarization refers to the existence of electric domains in ferroelectrics, electric domains refer to small regions with the same spontaneous polarization direction, and the boundaries between electric domains and electric domains are called domain walls. It is also urgent to study the dynamic structure of the surrounding rocks of heavy-duty railways. This article aims to study the use of nanomaterial and ferroelectric domain technology to improve the overall strength, wear resistance, toughness, and other properties of steel to ensure the safety of the surrounding rock dynamic structure of the heavy-duty railway in the small clearance intersecting tunnel. Moreover, on this basis, this article proposes the method of spraying steel with nanomaterials and the use of ferroelectric domain polarization technology. The strength and wear resistance of steel can be improved under different nanomaterial content and the degree of ferroelectric domain polarization. Sustainability and toughness have been improved, respectively. After the wear resistance experiment and analysis, the experimental results of this article show that the impact resistance of the steel increased by 18.75%. When 0.012% of CeO2 is added, the impact toughness of the steel is increased to the maximum of 3.4 J, an increase of 16.31%, and a 37% increase in wear resistance. Under the premise of ensuring the demand for heavy-duty transportation, the safety performance and sustainability of transportation are greatly improved.